Sum of Divisors in a Ring of Gaussian Integers - Sinyavskii, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We construct an asymptotic formula for a sum function for σ a (α), where σ a (α) is the sum of the ath powers of the norms of divisors of the Gaussian integer α on an arithmetic progression α ≡ α0 (mod γ) and in a narrow sector ϕ1 ≤ arg α < ϕ2. For this purpose, we use a representation of σ a (n) in the form of a series in the Ramanujan sums.